Multi-centric longitudinal study on electrophysiological diagnostic and prognostic markers in prolonged disorders of consciousness. Issue 1 (January 2019) - Estraneo, A.; Fiorenza, S.; Masotta, O.; Grippo, A.; Romoli, A.; Formisano, R.; Mattia, D.; Angelakis, E.; Cassol, H.; Thibaut, A.; Gosseries, O.; Blandiaux, S.; et al.
Abstract : Diagnostic accuracy and reliable assessment of prognosis are challenging in patients in vegetative state (VS) and in minimally conscious state (MCS). This longitudinal multi-centric study aims to identify neurophysiological patterns with diagnostic and prognostic value. 59 patients in VS and 63 in MCS underwent clinical assessment by Coma Recovery Scale-Revised 3 and neurophysiological evaluations of EEG background activity and reactivity, somatosensory evoked potential (SEP) and event related potential (ERP) at ⩽3 months after brain-injury. Clinical outcome was evaluated at 6 months post-injury. EEG background activity and reactivity significantly differed between VS and MCS patients (p < .001), whereas the presence of cortical component N20 on SEP and P300 on ERP did not differ between the two groups. Good outcome was significantly more frequent in patients with moderately abnormal to normal EEG background activity than in patients with poor EEG background organization (p = .001), in patients showing EEG reactivity (p < .001) and in patients showing P300 (p = .016). The presence of SEP did not differ significantly between the two prognostic groups. Multimodal clinical and neurophysiological assessment could provide useful diagnostic and prognostic information for disorder of consciousness. This multicentric project calls for international standardization of diagnostic and prognostic procedures.